Proceedings of the 2020 SIAM International Conference on Data Mining 2020
DOI: 10.1137/1.9781611976236.51
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Aware Answers of the Crowd

Abstract: Crowdsourcing is a relatively economic and efficient solution to collect annotations from the crowd through online platforms. Answers collected from workers with different expertise may be noisy and unreliable, and the quality of annotated data needs to be further maintained. Various solutions have been attempted to obtain high-quality annotations. However, they all assume that workers' label quality is stable over time (always at the same level whenever they conduct the tasks). In practice, workers' attention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…This process is human-resource intensive and requires expertise in the subject area, in which the annotation takes place. In recent years, crowdsourcing has been used to alleviate the demand of elaborate human expertise [39].…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…This process is human-resource intensive and requires expertise in the subject area, in which the annotation takes place. In recent years, crowdsourcing has been used to alleviate the demand of elaborate human expertise [39].…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…General user attention covers the overall attention a user gives to an user interface without considering the task-specific information. Studies have shown that general user attention improves human performance in different work and play activities [45], [46]. We hypothesize that crowdsourcing is another workrelated activity that demands user attention for carrying out the tasks well.…”
Section: Research Objectivesmentioning
confidence: 96%
“…CrowdDQS dynamically issues golden standard questions and estimate the accuracies of workers in real-time, then it can select workers with higher accuracies for task assignment [14]. Tu et al suggest that the attention of workers changes over time, thus the accuracy of workers can not be kept constant, therefore, they proposed a probabilistic model that takes into account workers' attention [38]. Compared to these models, this paper focuses on a different attention weights in COR scenario and our assumption is that the ability of a worker is diverse but constant (i.e.…”
Section: Crowdsourcingmentioning
confidence: 99%